2009
DOI: 10.1143/jjap.48.071501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermoelectric Properties of Polythiophene Films Synthesized by Electrolytic Polymerization

Abstract: Polythiophene films were synthesized by electrolytic polymerization, and the synthetic parameters and their thermoelectric properties, i.e., Seebeck coefficient and electric conductivity, were investigated in detail. The Seebeck coefficient tended to decrease with increasing electric conductivity. However, the thermoelectric power factor increased with electric conductivity, and was 1:03 Â 10 À5 WÁm À1 ÁK À2 at 23 mVÁK À1 and at 201 SÁcm À1 . This value is large compared with those of other conductive polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…Here, an extremely low thermal conductivity (0.33 ± 0.02 W m −1 K −1 ) was determined on freestanding samples via the self‐heating 3ω method for samples with a conductivity of 565 ± 15 S cm −1 and Seebeck coefficient of 42 ± 1 µV K −1 under room temperature. The maximum ZT value can reach up to 0.10, which is about three times higher than previous reports, showing the great potential of PTh to serve as the active material for construction of flexible and wearable TE generators.…”
mentioning
confidence: 58%
“…Here, an extremely low thermal conductivity (0.33 ± 0.02 W m −1 K −1 ) was determined on freestanding samples via the self‐heating 3ω method for samples with a conductivity of 565 ± 15 S cm −1 and Seebeck coefficient of 42 ± 1 µV K −1 under room temperature. The maximum ZT value can reach up to 0.10, which is about three times higher than previous reports, showing the great potential of PTh to serve as the active material for construction of flexible and wearable TE generators.…”
mentioning
confidence: 58%
“…Studies reported in literature indicate that the unfilled PTh has a monoclinic or orthorhombic crystal structure . Experimental parameters used in the polymerization of the PTh and its derivatives can affect their crystal structure or lattice parameters .…”
Section: Resultsmentioning
confidence: 99%
“…Shinohara et al found that the electrical conductivity of PTh was more sensitive to the experimental conditions than its Seebeck coefficient. [69] The PTh films with high crystallinity can exhibit an electrical conductivity of 201 S cm −1 and PF of 10.3 μW m −1 K −2 . Xu et al modified the electrochemical polymerization conditions of PTh, poly(3-methylthiophene) (P3MeT), and poly(3octylthiophene) (P3OT) by adding 2,6-di-tert-butylpyridine (DTBP, chemical structure shown in Figure 2c) into the polymerization solution.…”
Section: Te Properties Of Polythiophenes By Electrochemical Polymerizmentioning
confidence: 99%
“…The properties of the polymer films, such as the electrical conductivity and Seebeck coefficient, depend on the polymerization conditions. Shinohara et al found that the electrical conductivity of PTh was more sensitive to the experimental conditions than its Seebeck coefficient . The PTh films with high crystallinity can exhibit an electrical conductivity of 201 S cm −1 and PF of 10.3 µW m −1 K −2 .…”
Section: P‐type Te Polymersmentioning
confidence: 99%